Problematyka dostępu do zawodu sędziego a jurysprudencja cnót - Zaorski, Adrian (PRAWO i WIĘŹ, 2025)
The subject of this paper from the philosophy of law is the regulation of access to the judicial profession, due to its impact on the operation of the judiciary. The purpose of the analyses carried out is to evaluate the current regulation from the point of view offered by virtue jurisprudence. The paper reconstructs the current ways of reaching the position of judge, the theoretical background offered by virtue jurisprudence and the formulation of theses on moral development. This made it possible to assess the different ways of entering the judiciary. Equally positive was the form of access to the judiciary through primary and supplementary application, as opposed to the possibility of „transition” from another legal profession. As part of the conclusions, postulates of a de lege lata and de lege ferenda nature were pointed out and an area of research was identified that should be the subject of further research, including empirical research.